A new modeling of human joint lubrication subject to shock loading - Bou-Saïd, Benyebka (European Journal of Computational Mechanics, 2005)
This article involves the study of a knee, hip or shoulder joint subject to shock loading or sudden inception of simple shear. Human joints are lubricated by synovial fluid. To properly model joint performance, one must take into account the behavior of this fluid in response to sudden changes. Recent developments in the rheological characterization of polymer fluids suggest an extrapolation of their behavior to biological fluids. Based on a microstructural description of the fluid, it is possible to establish laws of rheological behavior to reproduce shock or sudden inception of shear phenomenon, taking into account large deformation and viscoelastic effects. Consideration of rheological behavior is likely necessary to characterize the response of synovial fluid to shock or sudden variation of applied force. The response of synovial fluid to a sudden overload is analyzed. Modeling of the resulting flow requires the use of nonlinear tensor relationships. The results obtained for various shock amplitude and duration are related to internal parameters of the model, parameters which can be connected to the health and the age of the individual.